Teaching Certified Translator Candidates at the Adam Mickiewicz University in Poznań, Poland - Gortych-Michalak, Karolina; Matulewska, Aleksandra (My University, 2014)
The curriculum of a post-graduate course at the Adam Mickiewicz University has been prepared after an analysis of translation problems occurring in EU legal translations into Polish. An introduction to civil law, commercial law, civil procedure, penal law and penal procedure has been included in the curriculum. A Polish language course has also been introduced as the analysis also revealed that many errors result from insufficient knowledge of the mother tongue. The course includes legal translation strategies and methodology, and also solutions for the most frequently occurring grammatical, stylistic and punctuation problems. Students are acquainted with the rules recommended by the Sworn Translators' Code and the macrostructure of legal texts formulated in Polish and foreign languages and also non-legal texts translated for courts, the public prosecution service and the police. The presentation is intended to show methods applied by legal translation teachers of various pairs of languages to overcome the main translation problems with special emphasis placed on avoiding fatal errors.
New Tasks For Legal Interpreters and Translators in the Enlarged Europe. Proceedings from the international conference, Kraków, 3-5 April 2014.The Polish Society of Sworn and Specialised Translators TEPIS
Keywords: Translation teaching; Legal Translation; Post-graduate Pranslation Course